the Physical properties of water and air in Basrah, southern Iraq - Abdulah , Prof Sadiq Salim; Lafta, Ali Abdulridha (Thi Qar Arts Journal, 2024)
The Shatt al-Arab is one of the vital rivers in southern Iraq, it is an important source of fresh water for Basra province. The Shatt al-Arab is a tidal river and the type of tide is mixed, prevailing semidiurnal . The physical characteristic of water and air are important topics that represent one of the components of a healthy environment for the residential areas in which it is located. On the banks of rivers, since these rivers are the lungs of life for the population, the values ​​of these variables may differ according to the geographical location of the river. The current study provides an insight into the physical variables of water and air in two different locations of the Shatt al-Arab and knowledge of the behavior of those variables in these two places. The data was collected through Two stations were installed by a team from the Marine Science Center - University of Basra. These two stations are of the HOBO type. The results showed that there is a difference in the values ​​of these characteristic in the northern part of the river and in the central part of it, where the northwestern winds are dominant in the study area, followed by the southern winds. Eastern, the highest wind value reaches 26.1 km/hr., and this value causes the generation of waves in the Shatt al-Arab. These winds also work to erosion the banks of the river in some places. Temperature values ​​ indicates that they are very high, including extremes that exceeded fifty degrees Celsius, it is a negative factor to loss of quantities of river water due to evaporation. According to the salinity changes in the two stations, Al-Qurna station can be considered a freshwater river station, while Al-Ashar station can be considered, in many periods, as a part of the head of the Shatt Al-Arab estuary . The effect of tidal phenomena was more clear in Al-Ashar station than in Al-Qurna station ..